Exposure to Second-hand tobacco smoke and health impact assessment of consumption transition from conventional cigarettes to new nicotine containing devices - Meisutovic-Akhtarieva, Marija; Kauneliene, Violeta; Prasauskas, Tadas; Martuzevicius, Dainius; Christophi, Costas A. (My University, 2020)
The use of novel nicotine-containing devices as an alternative to conventional cigarettes is increasing rapidly. This raises many questions on the potential effects of this transition to both mainstream smokers and bystanders. The aim of this study was to investigate dynamics of aerosol generated by use of different nicotine containing products. The findings of this study will provide new evidence to scientists, health care professionals, and smokers that may help differentiate among the different alternatives. The laboratory simulation of the dispersion of exhaled tobacco products aerosol was conducted in an indoor chamber with controlled environmental conditions.
Keywords: Aerosol; Indoor air quality; Nicotine-containing products; THS